Femtosecond laser–assisted cataract surgery compared with phacoemulsification cataract surgery: randomized noninferiority trial with 1-year outcomes. Issue 10 (October 2020) - Day, Alexander C.; Burr, Jennifer M.; Bennett, Kate; Doré, Caroline J.; Bunce, Catey; Hunter, Rachael; Nanavaty, Mayank A.; Balaggan, Kamaljit S.; Wilkins, Mark R.
Abstract : The outcomes of FLACS are similar to those of phacoemulsification cataract surgery at 1-year follow-up. FLACS was not cost-effective. Abstract : Purpose: To report the 1-year outcomes of a randomized trial comparing femtosecond laser–assisted cataract surgery (FLACS) and phacoemulsification cataract surgery (PCS). Setting: Moorfields Eye Hospital, New Cross Hospital, and Sussex Eye Hospital, United Kingdom. Design: Multicenter, randomized controlled noninferiority trial. Methods: Patients undergoing cataract surgery were randomized to FLACS or PCS. Postoperative assessments were masked. Outcomes included uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), complications, corneal endothelial cell count, and patient-reported outcomes measures. Results: The study enrolled 785 participants. A total of 311 of 392 (79%) participants were allocated to FLACS and 292 of 393 (74%) participants were allocated to PCS attended follow-up at 1 year. Mean UDVA was 0.14 (SD = 0.22) for FLACS and 0.17 (0.25) for PCS with difference of −0.03 logarithm of the minimum angle of resolution (logMAR) (95%, −0.06 to 0.01, P = .17). Mean CDVA was 0.003 (0.18) for FLACS and 0.03 (0.23) for PCS with difference of −0.03 logMAR (95% CI, −0.06 to 0.01, P = .11); 75% of both FLACS (230/307) and PCS (218/290) cases were within ±0.5 diopters (D) refractive target, and 292 (95%) of 307 eyes of FLACS and 279 (96%) of 290 eyes of PCS groups were within ±1.0 D. There were no significant differences between arms for all other outcomes with the exception of binocular CDVA mean difference −0.02 (−0.05 to 0.002) logMAR ( P = .036) favoring FLACS. Mean cost difference was £167.62 per patient greater for FLACS (95% iterations between −£14.12 and £341.67). Conclusions: PCS is not inferior to FLACS regarding vision, patient-reported health, and safety outcomes after 1-year follow-up. A difference was found for binocular CDVA, which, although statistically significant, was not clinically important. FLACS was not cost-effective.